2013
DOI: 10.1080/13607863.2013.791661
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors of treatment response to cognitive-behavior therapy for late-life depression: an exploratory study

Abstract: Objective The primary objective of this study was to examine a variety of potential predictors of response to Cognitive Behavioral Therapy (CBT) in depressed older adults. Method Sixty older adults with a clinical diagnosis of major or minor depression or dysthymic disorder received 12 individual sessions of CBT over a 3 to 4 month period. The BDI-II was administered pre and post intervention to assess change in level of depression. A cut-off score of 13 or less at post was used to determine positive treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 49 publications
1
9
0
1
Order By: Relevance
“…This investigation includes 51 individuals (17 men and 34 women), who participated in a larger study of 60 participants (Marquett et al., ). Excluded participants (with incomplete information) did not significantly differ from the rest of the sample with regard to demographics.…”
Section: Methodssupporting
confidence: 90%
See 1 more Smart Citation
“…This investigation includes 51 individuals (17 men and 34 women), who participated in a larger study of 60 participants (Marquett et al., ). Excluded participants (with incomplete information) did not significantly differ from the rest of the sample with regard to demographics.…”
Section: Methodssupporting
confidence: 90%
“…Although CBT is effective at alleviating MDD, questions remain as to whether it similarly promotes meaning making. Drawing on Holland, Currier, Coleman, & Neimeyer's () Integration of Stressful Life Experiences Scale (ISLES), this study explored whether a CBT intervention with demonstrated efficacy for addressing geriatric depression (Marquett et al., ) also enhanced clients’ meaning made of stress. Demographic factors were examined as potential moderators of these changes.…”
Section: Introductionmentioning
confidence: 99%
“…A key goal of CBT is to improve the ability to regulate negative affect in the face of both daily and major stressful events. Importantly, CBT is effective at reducing older caregiver distress and improving performance on care-related tasks to which anxiety about failure is attached (Marquett et al, 2013).…”
mentioning
confidence: 99%
“…Furthermore, it would be interesting that future studies investigate factors that influence the response to psychotherapy in elders. Marquett et al () investigated psychosocial predictors of CBT response for LLD and suggest that individuals who showed greater improvement were more open to new experiences, less negatively affected by past stressors, more likely to cite others as responsible for negative stress in their lives and to seek emotional support when symptomatic.…”
Section: Discussionmentioning
confidence: 99%